Песни для голоса в сопровождении фортепиано и баяна - Высоцкий Владимир Семенович (РГБС, 2012)
Экземпляры: БС (20170303) / Инвентарный номер: РТШ53114 / Цена: 100.00 / Сис.шифр: 85.31 / Авт.знак: В 93 / ГРНТИ: 18.41 / ББК: 85.31